Factors and Mechanism Affecting the Attractiveness of Public Transport: Macroscopic and Microscopic Perspectives - Chunqin Zhang (Journal of Advanced Transportation, 2022)
Enhancing the attractiveness of public transport is a key objective for transit agencies that seek to achieve sustainable urban mobility. This study identifies the key factors that affect the attractiveness of public transport from the macroscopic and microscopic perspectives and establishes a comprehensive influence mechanism. Weighted least square-Structural equation model (WLS-SEM) is used to quantify the microscopic factors. Conclusions are summarized as follows: ① the macroscopic factors include urban spatial layout, land use pattern, geographical environment, level of economic development, demographic characteristics, public policy, and service characteristics of public transport; ② the microscopic factors include traveler’s individual characteristics, travel demand characteristics, travel characteristics and service level of public transport; ③ service level of public transport most positively impacts the attractiveness, while the travel characteristics of public transport impact it most negatively.